A Family of Superhelicenes: Easily Tunable, Chiral Nanographenes by Merging Helicity with Planar pi Systems - Reger, David; Haines, Philipp; Amsharov, Konstantin; Schmidt, Julia A.; Ullrich, Tobias; Bönisch, Simon; Hampel, Frank; Görling, Andreas; Nelson, Jenny; Jelfs, Kim E.; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2021)
We designed a straightforward synthetic route towards a full-fledged family of pi-extended helicenes: superhelicenes. They have two hexa-peri-hexabenzocoronenes (HBCs) in common that are connected via a central five-membered ring. By means of structurally altering this 5-membered ring, we realized a versatile library of molecular building blocks. Not only the superhelicene structure, but also their features are tuned with ease. In-depth physico-chemical characterizations served as a proof of concept thereof. The superhelicene enantiomers were separated, their circular dichroism was measured in preliminary studies and concluded with an enantiomeric assignment. Our work was rounded-off by crystal structure analyses. Mixed stacks of M- and P-isomers led to twisted molecular wires. Using such stacks, charge-carrier mobilities were calculated, giving reason to expect outstanding hole transporting properties.
CRIS-Team WoS Importer:2021-07-23

Controlling and Fine-Tuning Charge-Transfer Emission in 2,6-Dicyanoaniline Multichromophores Prepared through Domino Reactions: Entry to a Potentially New Class of OLEDs - Plass, Fabian; Bönisch, Simon; Held, Felix; Ullrich, Tobias; Fischer, Florian; Guryev, Anton; Görling, Andreas; Kahnt, Axel; Tsogoeva, Svetlana (Journal of Organic Chemistry, 2021)
Substituted 2,6-dicyanoanilines are versatile electron donor-acceptor compounds, which have recently received considerable attention, since they exhibit strong fluorescence and may have utility in the synthesis of fluorescent materials, non-natural photosynthetic systems, and materials with nonlinear optical properties. The majority of known synthetic procedures are, however, "stop-and-go"reaction processes involving time-consuming and waste-producing isolation and purification of product intermediates. Here, we present the synthesis of substituted 2,6-dicyanoanilines via atom-economical and eco-friendly one-pot processes, involving metal-free domino reactions, and their subsequent photochemical and photophysical measurements and theoretical calculations. These studies exhibit the existence of an easily tunable radical ion pair-based charge-transfer (CT) emission in the synthesized 2,6-dicyanoaniline-based electron donor-acceptor systems. The charge-transfer processes were explored by photochemical and radiation chemical measurements, in particular, based on femtosecond laser photolysis transient absorption spectroscopy and time-resolved emission spectroscopy, accompanied by pulse radiolysis and complemented by quantum chemical investigations employing time-dependent density-functional theory. This chromophore class exhibits a broad-wavelength-range fine-tunable charge recombination emission with high photoluminescence quantum yields up to 0.98. Together with its rather simple and cost-effective synthesis (using easily available starting materials) and customizable properties, it renders this class of compounds feasible candidates as potential dyes for future optoelectronic devices like organic light-emitting diodes (OLEDs).
CRIS-Team Scopus Importer:2021-05-14

Deeper Insight into the Six-Step Domino Reaction of Aldehydes with Malononitrile and Evaluation of Antiviral and Antimalarial Activities of the Obtained Bicyclic Products. - Bock, Christina; Gangajji, Parameshwarappa; Bönisch, Simon; Bauer, Walter; Hutterer, Corina; Leidenberger, Maria; Friedrich, Oliver; Marschall, Manfred; Kappes, Bärbel; Görling, Andreas; Tsogoeva, Svetlana (ChemistryOpen, 2017)
The straightforward and efficient synthesis of complex aza- and carbobicyclic compounds, which are of importance for medicinal chemistry, is a challenge for modern chemical methodology. An unprecedented metal-free six-step domino reaction of aldehydes with malononitrile was presented in our previous study to provide, in a single operation, these bicyclic nitrogen-containing molecules. Presented here is a deeper investigation of this atom-economical domino process by extending the scope of aldehydes, performing post-modifications of domino products, applying bifunctional organocatalysts and comprehensive NMR studies of selected domino products. The thermodynamic aspects of the overall reaction are also demonstrated using DFT methods in conjunction with a semi-empirical treatment of van der Waals interactions. Furthermore, biological studies of seven highly functionalized and artemisinin-containing domino products against human cytomegalovirus (HCMV) and Plasmodium falciparum 3D7 are presented. Remarkably, in vitro tests against HCMV revealed five domino products to be highly active compounds (EC50 0.071-1.8 μm), outperforming the clinical reference drug ganciclovir (EC50 2.6 μm). Against P. falciparum 3D7, three of the investigated artemisinin-derived domino products (EC50 0.72-1.8 nm) were more potent than the clinical drug chloroquine (EC50 9.1 nm).

Elucidating activating and deactivating effects of carboxylic acids on polyoxometalate-catalysed three-phase liquid–liquid-gas reactions - Poller, Maximilian J.; Bönisch, Simon; Bertleff, Benjamin; Raabe, Jan Christian; Görling, Andreas; Albert, Jakob (Chemical Engineering Science, 2022)
Three-phase liquid–liquid gas reactions are promising strategies to combine highly active and selective homogeneous-catalysed oxidation reactions with in-situ product isolation. Several approaches like the three-phasic oxidation of biomass to formic acid (OxFA process) or the three-phasic extraction-coupled oxidative desulfurization (ECODS process) of fuels have been developed. Hereby, an aqueous polyoxometalate (POM) catalyst solution in combination with molecular oxygen as oxidant is used. However, contrary effects on the oxidation performance of the POM-catalyst were observed for different carboxylic acids as reaction products or intermediates. By using model calculations employing Density-Functional Theory (DFT) in combination with magnetic and optical spectroscopy, we could explain the experimental observations that oxalic acid activates the POM catalyst and therefore promotes its oxidation performance while acetic and especially formic acid form stable complexes with the active centres and therefore inhibit the oxidation activity. These findings greatly improve the understanding of POM-acid complexes and their effect on the catalytic performance.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Catalyst activation/deactivation; Density-functional calculations; Polyoxometalates; Spectroscopic investigations; Three-phase liquid–liquid-gas reactions

Facile Access to Challenging ortho-Terphenyls via Merging Two Multi-Step Domino Reactions in One-Pot: A Joint Experimental/Theoretical Study - Grau, Benedikt; Bönisch, Simon; Neuhauser, Alexander; Hampel, Frank; Görling, Andreas; Tsogoeva, Svetlana (ChemCatChem, 2019)
ortho-Terphenyls are of high interest for medicinal chemistry and materials science, but they are difficult to access. Herein, we demonstrate a straightforward and sustainable synthesis of highly functionalized ortho-terphenyls via joining an organocatalyzed two-step domino reaction (Knoevenagel/vinylogous Michael) with a DABCO/CuBr2 co-catalyzed three-step domino reaction (cyclization/tautomerization/aromatization) in a one-pot process. Overcoming necessity to isolate intermediate products leads to a reduction of energy, costs and waste for a broad scope of reactions. DFT calculations have been performed to investigate the thermodynamics of this one-pot process towards ortho-terphenyls and to study the reaction profile of the vinylogous Michael reaction under inclusion of solvent effects. Role of London dispersion forces in this transformation has been elucidated. It is shown that reaction kinetics and thermodynamics are slightly influenced by dispersion interactions. Furthermore, the addition of dispersion energy donors leads to small changes of reaction energies in some cases.
CRIS-Team WoS Importer:2019-08-23

Generation of Complex Azabicycles and Carbobicycles from Two Simple Compounds in a Single Operation through a Metal-Free Six-Step Domino Reaction - Bock, Christina; Parameshwarappa, Gangajji; Bönisch, Simon; Neiß, Christian; Bauer, Walter; Hampel, Frank; Görling, Andreas; Tsogoeva, Svetlana (Chemistry - A European Journal, 2016)
Aza- and carbobicyclic compounds possess favorable pharmaceutical properties, but they are difficult to access. Herein, we demonstrate an unprecedented organocatalytic two component six-step chemodivergent domino reaction, which provides a straightforward, sustainable and atom economical route to difficult-to-access complex bicyclic architectures: azabicycles and carbobicycles, whose ratios can be controlled by the applied electrophiles and catalysts. Detailed NMR and X-ray studies on the structures and relative stereochemistry of selected compounds are presented. Mechanistic investigations of the chemoselective branching step have been carried out with DFT methods in conjunction with semiempirical van der Waals interactions. This new domino reaction opens up a new vista of generating, in a single operation, new bioactive compounds with strong antiviral properties (EC50 up to 0.071 μM for human cytomegalovirus (HCMV)) outperforming clinically used ganciclovir (EC50 2.6 μM).
Keywords: antiviral agents; density functional calculations; domino reaction; medicinal chemistry; organocatalysis

Screening Nanographene-Mediated Inter(Porphyrin) Communication to Optimize Inter(Porphyrin–Fullerene) Forces - Haines, Philipp; Kaur, Ramandeep; Martin, Max; Minameyer, Martin; Frühwald, Stefan; Bönisch, Simon; Lungerich, Dominik; Hampel, Frank; Görling, Andreas; Drewello, Thomas; Jux, Norbert; Guldi, Dirk Michael (Advanced Energy Materials, 2021)
Multifunctional molecular materials comprising porphyrins and fullerenes have served as perfect prototypes to study key aspects of natural photosynthesis starting at light harvesting and energy transfer processes all the way to charge separation, charge shift, and charge recombination. Herein, hexa-peri-hexabenzocoronenes (HBCs) are explored, decorated with one, two, and six porphyrins at their peripheral positions, within the context of replicating key steps of photosynthesis. The major focus of the investigations is to screen inter(porphyrin) communications across the HBC platform as a function of the substitution pattern and to optimize the intermolecular forces with fullerenes. To this end, the ground- and excited-state features are investigated in the absence of C60 and C70 by employing an arsenal of spectroscopic methods. Further insights into inter(porphyrin) communications come from time-dependent density-functional theory (TDDFT) calculations. In the presence of C60 and C70, X-ray crystallography, steady-state and time-resolved spectroscopy, and mass spectrometry corroborate exceptionally strong inter(porphyrin–fullerene) interactions in the solid, liquid, and gas phases. The experiments are backed-up with DFT calculations of the geometrically optimized and energetically stable complex configuration.
CRIS-Team Scopus Importer:2021-03-26
Keywords: charge separation; crystal structure; fullerene; hexabenzocoronene; porphyrin; transient absorption